A study on awareness of universal precautions among house surgeons - Kulkarni, Rajesh R.; Biradar, Mallikarjun (International Journal Of Community Medicine And Public Health, 2018)
Background: Health-care workers are at risk of many infections at their workplace through airborne, blood borne, fecal-oral transmission and direct contact. Universal precautions are not well understood or implemented by health care practitioners. The knowledge and understanding of UPs among HCWs in developing countries is inadequate. The study was done to assess the awareness of universal precautions among the house surgeons and knowledge about precautionary measures. Methods: The present questionnaire based cross sectional study was carried out on the house surgeons who were posted in the department of community medicine, KLE University’s J N medical college, Belagavi. A total of 136 house surgeons were interviewed. Pretested, pre designed multiple response type questionnaire were administered to them. Results: Out of 136 study participants, 118 (87%) have heard about the term universal precautions, 118 (87%) self protection against body and blood fluids. 113 (83.1%) have correctly answered about precautionary measures for internal body fluids. Disposal of sharp items, 117 (86.1%) have told puncture proof container should be used, 128 (94.1%) have answered to use gowns, face mask to avoid splashing of blood while doing procedures. and 100 (73.5%) have told to apply universal precautions even on HIV–ve patients. Conclusions: The awareness about universal precautions among the study subjects was good in some aspects but not satisfactory in many others.